Penggunaan Fraud Hexagon dalam Mendeteksi Kecurangan Laporan Keuangan - Didi Setyono; Eko Hariyanto; Sri Wahyuni; Bima Cinintya Pratama (Politeknik Ganesha Medan, 2023)
This research aims to examine the fraud hexagon theory in the detection of fraudulent financial reporting that occurs in a company. According to the hexagon fraud theory, fraud occurs due to 6 factors, namely pressure/stimulus, opportunity, capability, ego/arrogance, rationalization, and collusion. These 6 factors are proxied with 10 proxies, namely: financial stability, financial targets, external pressure, change in director, change in auditor, ineffective monitoring, industry nature, number of CEO photos, political connections, and collusion. The population in this research are companies listed in the LQ 45 index period I February-July 2017-2021. The sample in this study is 88 samples. The data analysis approach used is statistic descriptive, classic assumption test, and multiple regression analysis using SPSS 25. The results of this study reveal that the nature of industry and external pressures have a negative effect on the detection of financial statement fraud, and change in auditor positively effect on the detection of financial statements fraud. While the variables of financial stability, financial targets, political connections, change in directors, number of CEO photos, ineffective monitoring, and collusion have no effect in detecting financial statements fraud. This result can be used for companies management as their references about what makes fraudulent financial statements occurs, so they can make preventive action for their companies